Nearest-Neighbors Matching for Case–Control Study Analyses: Better Risk Factor Identification From a Study of Sporadic Campylobacteriosis in the United States. Issue 5 (13th May 2022) - Cui, Zhaohui; Marder, Ellyn P.; Click, Eleanor S.; Hoekstra, Robert M.; Bruce, Beau B.
Abstract : Background: Case–control studies are commonly used to explore factors associated with enteric bacterial diseases. Control of confounding is challenging due to a large number of exposures of interest and the low frequencies of many of them. Methods: We evaluated nearest-neighbors matching in a case–control study (originally 1:1 matched, published in 2004) of sporadic Campylobacter infections that included information on 433 exposures in 2632 subjects during 1998–1999. We performed multiple imputations of missing data (m = 100) and calculated Gower distances between cases and controls using all possible confounders for each exposure in each dataset. We matched each case with ≤20 controls within a data-determined distance. We calculated odds ratios and population attributable fractions (PAFs). Results: Examination of pairwise correlation between exposures found very strong associations for 1046 pairs of exposures. More than 100 exposures were associated with campylobacteriosis, including nearly all risk factors identified using the previously published approach that included only 16 exposures and some less studied, rare exposures such as consumption of chicken liver and raw clams. Consumption of chicken and nonpoultry meat had the highest PAFs (62% and 59%, respectively). Conclusions: Nearest-neighbors matching appear to provide an improved ability to examine rare exposures and better control for numerous highly associated confounders.